Pengaruh Pengendalian Internal, Moralitas Individu Dan Budaya Etis Organisasi Pada Kecenderungan Kecurangan Akuntansi - Chandrayatna, I Dewa Gede Praditya; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p09, 2019)
This study aims to determine the effect of internal control, individual morality and organizational ethical culture on accounting fraud tendencies. This research is located at PT. Regional Development Bank (BPD) Bali. The population in this study were 236 employees of PT. BPD Bali. The number of samples used was 172 employees using the nonprobability sampling method specifically purposive sampling. Data was collected through survey methods with questionnaire instruments. The results of this research questionnaire were measured using a modified Likert scale. The data analysis technique used is multiple linear regression analysis techniques. Based on the results of multiple linear regression analysis, it is shown that internal control, individual morality and organizational ethical culture negatively influence accounting fraud tendencies. The implication of this research theoretically is supporting the theory of fraud triangle and the theory of moral development. Keywords: internal control, individual morality, organizational ethical culture, accounting fraud tendency